Answer: -630
Step-by-step explanation:
Given the nth term of a sequence;
a(n)=a(n−1)⋅(−9) and the first term of the sequence a(1) as 35, the third term of the sequence can be gotten by using the formula at when n = 3
If n = 3 and a(1) = 35;
a(3) = 35(3-1)•(-9)
a(3) = 35×2×-9
a(3) = 70×-9
a(3) = -630
There the 3rd term of the series will give us -630 according to the nth term of the formula given.
The problem is about a recursive sequence where each term is the previous term multiplied by -9. After applying this rule twice, it is found that the 3rd term of the sequence is 243.
The problem provided indicates a recursive sequence, where each term is based on the previous term. The sequence is defined as a(1) = 3 and a(n) = a(n - 1) ⋅ (−9), which essentially means that each subsequent term is the previous term multiplied by -9.
To find the 3rd term, we apply this rule twice starting from the first term:
a(2) = a(1) * (-9) = 3 * (-9) = -27
a(3) = a(2) * (-9) = -27 * (-9) = 243
Therefore, the 3rd term of the sequence is 243.
#SPJ3
Answer:
Option 3
Step-by-step explanation:
Brainliest please~
x = 4 and x = –4
x = 8 and x = –8
x = 16 and x = –16
The correct statement is that the solution of this equation x² – 16 = 0, is 4 and -4.
It is a polynomial that is equal to zero. Polynomial of variable power 2, 1, and 0 terms are there. Any equation having one term in which the power of the variable is a maximum of 2 then it is called a quadratic equation. The general form of the quadratic equation is ax² + bx + c = 0
Given
The quadratic equation x² – 16 = 0
To find
The root of the quadratic equtaion?
The quadratic equation x² – 16 = 0
We know the formula,
a² - b² = ( a - b ) ( a + b )
Then
x² – 4² = 0
(x - 4)(x + 4) = 0
x = 4 and -4
Thus, the solution of this equation x² – 16 = 0, is 4 and -4.
More about the quadratic equation link is given below.
Answer: The correct option is (B) x = 4 and x = -4.
Step-by-step explanation: We are given to find the solutions to the following quadratic equation :
Since the coefficient of x is zero in the given equation, so we will be using the method of square root to solve the equation.
From equation (i), we have
Thus, the required solution is x = 4 and x = -4.
Option (B) is correct.
JACK IS CORRECT.
4n²= 36 when n=3, not 144.
It is because you have to power up first, then you should multiply. But Katie did the opposite, so she was wrong.
Answer:
4
Step-by-step explanation:
2√x, √x + 1, 2√x + 1 sides of triangle
√x= y
2y, y+1, 2y+1
(2y)²+(y+1)²= (2y+1)²
4y²+y²+2y+1= 4y²+4y+1
y²-2y=0
y=0 (discarded as side can't be zero) or y= 2
so √x=2 ⇒ x= 4
Answer:
x= 4
According to the Pythagoras Theoram,
p²+b²= h²